Can professionals “keep the tiller straight” in organizations? Resistance to reframing and decoy alternatives in workplace decision-making - Angioletti, Laura; Acconito, Carlotta; Crivelli, Davide; Balconi, Michela (Frontiers in Psychology, 2024)
So far, little is known about the ability to contrast contextual bias as a protective factor in an ever-changing organizational environment. This study assessed whether professionals with different seniority can resist the reframing and the decoy effect under decision-making conditions, and if decision-making styles can predict the resistance to such covert influence tactics. Two groups of professionals divided into senior and junior professionals performed two novel tasks, a Resistance to Reframe Task (RRT) and a Resistance to Alternatives Task (RAT), that, by including ecological scenarios that represent typical decision situations that could arise in the company, can measure the resistance to such covert influence tactics. Decision-making styles were measured through the General Decision-Making Style (GDMS) and the Maximization Scale (MS). Results showed that all professionals could resist more to the reframing (at the RRT) than the decoy alternatives (RAT), without any difference between groups. Also, higher GDMS-dependent subscale scores predict lower RRT scores, especially in the group of senior professionals. While, in the group of junior professionals, the GDMS dependent subscale and MS high standards subscale predicted lower RAT scores. To conclude, this study showed that professionals know how to "keep the tiller straight" in organizations, especially when facing reframing conditions rather than decoy alternatives, however, the predominance of dependent decision-making styles (both for senior and junior professionals), and the tendency to hold high standards in decisions (mainly for juniors) could undermine their resistance capacity and make them vulnerable to these covert influence tactics.